The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s13054-023-04339-3
|View full text |Cite
|
Sign up to set email alerts
|

The end-tidal alveolar dead space fraction for risk stratification during the first week of invasive mechanical ventilation: an observational cohort study

Abstract: Background The end-tidal alveolar dead space fraction (AVDSf = [PaCO2−PETCO2]/PaCO2) is a metric used to estimate alveolar dead space. Higher AVDSf on the first day of mechanical ventilation is associated with mortality and fewer ventilator-free days. It is not clear if AVDSf is associated with length of ventilation in survivors, how AVDSf performs for risk stratification beyond the first day of ventilation, or whether AVDSf adds predictive value to oxygenation (oxygenation index [OI]) or sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…10,11 Physiological dead space (V D /V T ) is associated with outcomes in ARDS. [12][13][14] In a clinical study, Bhalla et al 15,16 found a good correlation between AVDSf and V D /V T in PARDS but had a large bias. Despite this, several studies demonstrated that AVDSf is an excellent indicator of alveolar dead space and has a strong association with mortality in PARDS after controlling for other markers of severity, such as hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Physiological dead space (V D /V T ) is associated with outcomes in ARDS. [12][13][14] In a clinical study, Bhalla et al 15,16 found a good correlation between AVDSf and V D /V T in PARDS but had a large bias. Despite this, several studies demonstrated that AVDSf is an excellent indicator of alveolar dead space and has a strong association with mortality in PARDS after controlling for other markers of severity, such as hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological dead space ( V D / V T ) is associated with outcomes in ARDS 12–14 . In a clinical study, Bhalla et al 15,16 found a good correlation between AVDSf and V D / V T in PARDS but had a large bias.…”
Section: Discussionmentioning
confidence: 99%
“…V T , PEEP, airway peak pressure (P peak ), airway mean pressure (P mean ), and Cdyn of the patients were also recorded. In addition, the arterial blood gas analyzer I‐STAT 300 (Abbott, USA) was used to record blood gas indicators and ventilation efficiency parameters, such as the arterial partial pressure of carbon dioxide (PaCO 2 ), oxygenation index (OI), respiratory index (RI), alveolar‐arterial oxygen partial pressure difference (A‐aO2), and dead space fraction (V D /V T ) during T 1 ‐T 3 11–13 . Parameters were calculated using the following equation: V D /V T = (PaCO 2 ‐P ET CO 2 )/PaCO 2 .…”
Section: Methodsmentioning
confidence: 99%